Application of Statistical Design of Experiment (SDE) to study wrinkles and delamination defects on composite sandwich panels - Muhammad Iqbal, Muhammad Hussain, Dr.; Zuraidah, Mohd Zain, Prof. Dr.; Mohd Shuid, Salleh; Chang, Lawrence (2012)
The sandwich panels made of composite materials are subject to a variety of process parameters. In this paper an experimental investigation of composite manufacturing significant issues; such as wrinkles and delamination on laminate and sandwich panels, will be carried out using Statistical Design of Experiment (SDE). The aim is to study the effects of delamination and wrinkling behaviour by optimizing temperature, pressure, soaking time, heat up and cool down rates and geometrical dimensions of honeycomb chamfer and using round off top surface honeycomb core vs. square. Whereby the process variables are to be set so as to get the smallest number of wrinkles and delaminate as possible. In this study it is proposed that Statistical Design of Experiments (SDE) is, in actual fact, a very useful technique for investigation of shop floor problem and setting of the process parameters with reduced variability. Instead of running many combinations of parameters in real life, SDE enables only a few combinations to be run before optimum process set-up can be determined. As a result, the time taken to determine optimum process set-up is greatly reduced. This also allows experimenters to get much more and much better data per experimental run.